2017
DOI: 10.1002/jib.392
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wort aeration on fermentation, maturation and volatile components of beer produced on an industrial scale

Abstract: The aim of the study was to determine the effect of the initial beer wort aeration on the process of fermentation, maturation, content of the volatile components of beer and abundance and vitality of yeast biomass. The experiments were performed on an industrial scale, with fermentation and maturation performed in fermentation tanks with a capacity of 3800 hL. The wort was aerated with sterile air in quantities as follows: 7, 10 and 12 mg/L. During fermentation and maturation, the changes in the content of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Furthermore, in their study, the increased pitching rate significantly reduced the acetaldehyde content in beer. In the previous works performed under conditions almost identical to those employed in this study, we reported quite similar findings [ 6 , 20 ]. However, in another experiment [ 19 ], the wort filling time had a significant, positive impact on the course of fermentation and the reduction in acetaldehyde concentrations.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, in their study, the increased pitching rate significantly reduced the acetaldehyde content in beer. In the previous works performed under conditions almost identical to those employed in this study, we reported quite similar findings [ 6 , 20 ]. However, in another experiment [ 19 ], the wort filling time had a significant, positive impact on the course of fermentation and the reduction in acetaldehyde concentrations.…”
Section: Resultssupporting
confidence: 90%
“…In our previous investigations [ 6 , 19 , 20 ], the effects of pitching rate, wort filling time, and wort aeration on fermentation, maturation, and volatile compound production in beer produced on an industrial scale were determined in single factor experiments. The purpose of the current work was therefore simultaneous optimization of these parameters by applying the RSM methodology.…”
Section: Introductionmentioning
confidence: 99%
“…During beer fermentation, yeast metabolism produces ethanol and carbon dioxide from a sugar-water mixture called wort [1,2]. The fermentation is conventionally monitored through off-line wort density measurements until a predetermined ethanol concentration is reached [3], after which the process is continued for a predefined time for development of flavour compounds [4]. This requires manual sampling, takes time, and wastes resources by disposing of the measured sample.…”
Section: Introductionmentioning
confidence: 99%
“…A necessary factor in the intensification of many technological, including biotechnological, processes is considered to be electromagnetic waves -waves that affect the growth, reproduction and fermentation energy of yeast-like fungi [11]. In the course of the study, the time dependence of the effect of X-ray radiation on the characteristics of the dependence of the degree of activation of the cell structures of the yeast culture of Saccharomyces cerevisiae was investigated and determined, which is shown in Table 1.…”
Section: Research Results and Discussionmentioning
confidence: 99%